Program Promosi Kesehatan “Food Smart Campus: Jadi Mahasiswa Sehat” - Yuwanda, Muhammad Fajar (YASIN, 2025)
This study is motivated by the limited research on improving healthy eating habits among university students through behavior modification approaches, despite the significant impact of diet on physical and mental health, particularly for final-year students. The aim of this research is to evaluate the effectiveness of a healthy eating education intervention based on the token economy system in improving students’ understanding and behavior regarding healthy eating. A quantitative method with a one-group pretest-posttest experimental design was used. The sample consisted of four final-year students selected through simple random sampling. Data were collected using a questionnaire developed based on the "Isi Piringku" guidelines from the Ministry of Health (2024) and an adapted instrument from previous studies. Data analysis was conducted using simple descriptive quantitative techniques. The results showed an increase in scores for both knowledge and healthy eating behavior after the intervention, indicating a positive impact of the education and token-based reinforcement on behavior change. These findings support Skinner’s theory of positive reinforcement, which emphasizes the role of consequences in shaping behavior. The main conclusion of this study is that the token economy approach is effective in fostering habits and discipline among students in adopting healthy eating patterns. The implications of this study contribute to the literature on behavioral interventions in health promotion and provide recommendations for educational institutions to develop similar programs to encourage healthy lifestyles among students. This research also opens opportunities for further studies to evaluate the long-term effectiveness of reinforcement-based interventions in the context of lifestyle changes. Keywords: healthy eating habits; final-year students; behavior modification; token economy